Information disorder and organic food purchasing behavior: A moderated mediation model - Zheng, Yan; Cao, Dayu (Frontiers in Nutrition, 2022)
On the one hand, fast social media and internet evolution has brought opportunities to the development of the organic food industry. On the other hand, the excessive utilization of social media and internet has also exerted some negative effects on consumers in terms of information disorder and hindered the industrial progression of organic foods. This study aimed to probe into the relationships between organic food information uncertainty, information search anxiety, information overload and purchase behavior under the mediating role of attitude and the moderating role of involvement, introducing the concept of information disorder in the context of this issue. The data (cross-sectional) of 620 organic food consumers in Jiangxi Province, China were subjected to SEM (structural equation modeling). The results showed that organic food information uncertainty and information search anxiety significantly affected attitude, and attitude had a positive impact on purchase behavior. In addition, attitude significantly mediated the effects of organic food information uncertainty and information search anxiety on purchase behavior. Moreover, the indirect relationship between organic food information uncertainty and purchase behavior was moderated by involvement.